Competencias digitales y aprendizaje autónomo de estudiantes de la Facultad de Ciencias de la Educación y Humanidades de la Universidad Nacional de la Amazonía Peruana 2025 - Ramos Santillan, Alberto (2025)
This study, conducted to determine the relationship between digital competencies and university students' autonomous learning, used a quantitative, explanatory, non experimental, and cross-sectional approach. The population consisted of 447 undergraduate students, representing a stratified probability sample of 207 participants. Two Likert-scale questionnaires were administered: one to measure digital competencies, with the following dimensions: information search and management, communication and collaboration, content creation, security, and problem-solving; and the autonomous learning variable, with the dimensions: expansion, collaboration, conceptualization, planning, exam preparation, and participation. The results showed a very high and significant positive correlation between digital competencies and autonomous learning (Spearman's Rho = 0.968; p < 0.001). The research concludes that the comprehensive strengthening of digital competencies directly enhances students' academic autonomy, which is key in the Amazonian context marked by technological and connectivity inequalities. It is recommended to implement cross curricular training programs in digital skills, ensure adequate technological infrastructure, and promote active methodologies that foster self-regulation and the creation of digital content.